Pengaruh Pemanfaatan Tekhnologi Informasi, Kualitas Sumber Daya Manusia Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintahan Desa Di Kabupaten Lombok Utara - Tutut Tri Andani; Baiq Kisnawati; Rusli Amrul (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to examine the influence of the use of information technology, the quality of human resources and the internal control system on the quality of village government financial reports in North Lombok district. The variables in this research consist of independent variables, namely the use of information technology (X1), quality of human resources (X2) internal control system (X3), and the dependent variable, namely the quality of village government financial reports in North Lombok district (Y). This type of research uses quantitative methods with an associative approach and collects primary data using questionnaire techniques which are measured using the Rikert scale. The population in this study was all village officials in North Lombok district, totaling 80 people. Sampling used a saturated sampling technique. The analysis technique used is Multiple Linear Regression with SPSS 25. The results of this study show that the use of information technology has an effect on the quality of village government financial reports in North Lombok district, while the quality of human resources and internal control systems has no effect on the quality of village government financial reports in the district. North Lombok. The R Square figure shows a value of 16.3% so that 83.7% is influenced by other variables.